Applications of Lasers in Various Fields Such as Communications, Energy and Medicine - shlaih Wahid, Badour abbas; Jumaah Kareem, Mohammed; Ali Kazem, Mohammed; Amir, Ali Salim Abdul; Othman Hassan, Aman Riaed (American Journal of Botany and Bioengineering, 2025)
Lasers are one of the achievements of human technology, which are beginning to find an increasingly broad application in various fields. Lasers, or “light amplification by stimulated emission of radiation”, are sources of optical radiation characterized by their extremely high output power, an extraordinary purity of the emitted radiation and the possibility of high spatial and spectral coherence of this radiation. There are many ways to establish the lasers by the type of active medium (gas, solid, semiconductor etc.), by the type of radiation emitted (continuous, pulsed, multimode, single-mode etc.), by the type of operating system (diode, marked, cutting, combining with fiber etc.), and by the wavelength in which they operate (infrared, visible, ultraviolet). Lasers have found and find a number of applications in everyday life in communications, construction, music, computer technology and others. The essay makes sense to focus on such technological applications of lasers, which can be especially promising for the future and whose appearance, to a large extent, is associated with the appearance of this new source of optical radiation. Areas where laser technology is already employed are included, in part because it is necessary to characterize the state of the art to appreciate what laser technology can replace and consolidate. However, emphasis is on more recent progress and predicted directions for technological advancement. These applications are considered together for each wavelength range and, when appropriate, also in relation to newly developed techniques for the generation of invisible infrared or ultraviolet radiations. Some aspects referring to one of the systems with which therapeutic procedures are carried out and considered briefly in one section are also discussed.